2009
DOI: 10.1002/app.31224
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy and contact angle studies of polymerizable gemini surfactant admicelles on mica

Abstract: Atomic force microscopy (AFM) was used to directly observe and characterize a polymer-modified mica surface prepared using a polymerizable gemini surfactant. Normal tapping mode and contact mode AFM were used to image the treated mica surface morphologies in air and liquid environments, respectively. The root mean square (RMS) roughness of mica surfaces before and after surface modification and polymerization was analyzed from these scans. To determine the effect of styrene adsolubilization on the surfactant-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…AFM measurements on mica and graphite surfaces reveal that the polymer film formation is indeed discontinuous. 46,50,56,57 In the case of the AFM images of our polymer-stabilized graphene, we observe an irregular deposition of the polymer on the graphene surface. The AFM images of irregular polymer deposition are similar to those of See et al and Marquez et al, 49,57 who observed polymerization on graphite surfaces.…”
Section: ' Results and Discussionmentioning
confidence: 80%
“…AFM measurements on mica and graphite surfaces reveal that the polymer film formation is indeed discontinuous. 46,50,56,57 In the case of the AFM images of our polymer-stabilized graphene, we observe an irregular deposition of the polymer on the graphene surface. The AFM images of irregular polymer deposition are similar to those of See et al and Marquez et al, 49,57 who observed polymerization on graphite surfaces.…”
Section: ' Results and Discussionmentioning
confidence: 80%
“…Poor adhesion between the polar filler surface and nonpolar polymer matrix results in inhomogeneous dispersion, insufficient reinforcement, and poor mechanical properties. To improve interfacial adhesion, one frequently used method is to treat inorganic fillers with coupling agents, such as stearic acid, silanes, zirconates, and titanates [10][11][12]. Another approach is to modify the chemistry of PP by attaching polar groups, for example, acrylic acid or maleic anhydride, onto the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, different mechanisms for the increased capacity in this study must be considered. Previous research supports the theory of an admicelle (micelle bilayer) formation by humic acids on the IEX acrylic resin surface when reused without regeneration (Asnachinda et al, 2010;Eastoe and Tabor, 2014).…”
Section: Iex Equilibria With Increasing Resin Loadingmentioning
confidence: 52%